Medidas de deslocamento do complexo hiolaríngeo pós-acidente vascular encefálico - Oliveira Neto, Isabella Christina [UNIFESP] (2019)
Introduction: hyoid bone and laryngeal displacement consist is an important in airway protective mechanism and allow safe feeding. Dysphagia is a common complication associated with laryngotracheal aspiration in Stroke. GOALS: to measure the maximum displacement of the hyoid bone (DH) and the larynx (DL) and the laryngeal hyoid distance (DHL) during swallowing in post-stroke patients and to compare them with the control group (CG), considering gender, age and laryngotracheal aspiration. Method: We recorded videofluoroscopic studies images of 27 post-stroke dysphagics, 15 female and 12 male, 7 adults and 20 elderly, 9 with laryngotracheal aspiration and 18 without. All with 5ml of pasty (n = 27) and when possible, 5ml of thin liquid (n = 16) and cheese bread (n = 18). The measurements were performed using the Image J program. The CG had 50 individuals, 25 females and 25 males. Results: Regarding the comparison between stroke group (SG) and group control group (CG), it was observed that SG showed significantly greater displacements compared to CG in DH (pasty and solid), DL (liquid, pasty and solid) and DHL at rest. The female SG presented significantly higher displacements of HD (solid); DL (liquid, pasty and solid); DHL at rest and percentage DHL (pasty) in relation to the female in the CG. The male SG presented significantly higher HD and DL (pasty) than the male CG. Adults in the SG presented significantly greater displacements of DH (pasty) and DL (pasty and solid) when compared to adults in the CG. The elderly in the SG obtained higher DL (pasty and solid) and the laryngeal hyoid distance (pasty) compared to the CG. It was found in the SG: DH (pasty) significantly higher in males than in females; DL showed no significant difference between sexes, age groups or presence or absence of laryngotracheal aspiration; DHL was significantly higher in males compared to females (pasty) and the percentage DHL was significantly higher in males compared to females (pasty). Conclusion: In relation to CG x stroke: DH was higher in the stroke group than in CG; The same was observed for female, male and adult groups. The DL was higher in the stroke group compared to the CG, as well as when comparing the female, male, adult and elderly groups. DHL at rest was higher in the stroke group than in the CG; The same was true of female groups. The% dHL was higher in the stroke group in the female and elderly groups. In the stroke group: DH, DHL and% dHL were higher in males than in females. It was not possible to differentiate the groups in relation to laryngotracheal aspiration.